(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study investigates the influence of electronic word of mouth (e-WOM) on the purchase decisions of Generation Z visitors in the seafood culinary tourism area of Kelan Beach, Bali. As digital natives, Generation Z relies heavily on peer-generated content and online reviews when making consumption decisions. Using a descriptive quantitative approach, data were collected from 100 purposively selected respondents who met the criteria of being active social media users and had visited Kelan Beach. The independent variable (e-WOM) was measured through intensity, valence of opinion, and content dimensions, while the dependent variable (purchase decision) was measured across product, brand, channel, timing, and amount. Simple linear regression analysis using SPSS revealed a strong and statistically significant influence of e-WOM on purchase decisions (R² = 0.764; p < 0.001). The findings highlight the strategic importance of managing digital narratives and online reputations in culinary tourism settings. The study contributes to understanding consumer behavior in digital environments and offers practical implications for destination marketers and culinary business operators.